"Augmented reality" applications in urology: a systematic review - Roberts, Sidney; Desai, Aditya; Checcucci, Enrico; Puliatti, Stefano; Taratkin, Mark; Kowalewski, Karl-Friedrich; Gomez Rivas, Juan; Rivero, Ines; Veneziano, Domenico; Autorino, Riccardo; Porpiglia, Francesco; Gill, Inderbir S.; et al. (Minerva urology and nephrology, 2022)
INTRODUCTION: Augmented reality (AR) applied to surgical procedures refers to the superimposition of preoperative or intraoperative images into the operative field. Augmented reality has been increasingly used in myriad surgical specialties including urology. The following study reviews advance in the use of AR for improvements in urologic outcomes. - EVIDENCE ACQUISITION: We identified all descriptive, validity, prospective randomized/nonrandomized trials and retrospective comparative/noncomparative studies about the use of AR in urology until March 2021. The Medline, Scopus, and Web of Science databases were used for literature search. We conducted the study selection according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis Statement) Guidelines. We limited included studies to only those using AR, excluding all that used virtual reality technology. - EVIDENCE SYNTHESIS: A total of 60 studies were identified and included in the present analysis. Overall, 19 studies were descriptive/validity/phantom studies for specific AR methodologies, 4 studies were case reports, and 37 studies included clinical prospective/retrospective comparative studies. - CONCLUSIONS: Advances in AR have led to increasing registration accuracy as well as increased ability to identify anatomic landmarks and improve outcomes during urologic procedures such as RARP and robot-assisted partial nephrectomy.